The semantic space of interest: the dative in Croatian - Stanojević, Mateusz-Milan (Array, 2014)
The Croatian dative is based on the notion of personal sphere (cf. Dąbrowska 1997), and stems from the old diachronic allative meaning, but is currently centered around the transfer prototype (e.g. verbs of giving, or communication), with extensions into the assessment pattern (meni je tamo bilo lijepo ‘I found it nice there’) and a reference point/affectedness pattern, including the dative of possession and ethical dative (roditelji su mu stanovali u Zagrebu ‘his parents lived in Zagreb’ ; Jesi li mi dobro? ‘Are you doing well (to me)?’) (Stanojević and Tuđman 2012). The differences between the patterns in Croatian have been primarily explained in terms of semantics (Stanojević and Geld 2007), as was the case with cognitive linguistic accounts of the dative in other Slavic languages (e.g. Janda 1993, Dąbrowska 1997). In this paper we focus on the use of clitic and non-clitic pronouns, claiming that it can be split into three groups based on a combination of syntactic and semantic factors. In the first group of patterns lexically governed by a verb, adjective or a noun (the allative, transfer and assessment patterns), both non-clitic and clitic forms can be used. Still, nouns governing the dative in the transfer pattern (e.g. pismo tebi ‘letter to you’, nagrada njemu ‘award to him’) are on the periphery of the group, because when combined with clitic pronouns they refer to the dative of possession or affectedness rather than transfer (e.g. pismo ti ‘your letter’) (also Mikaelian and Roudet 1999). The second group is the “dative of possession”, traditionally seen as a free dative, but in fact semantically governed by nouns that tend to be inalienable possessions in Croatian (cf. Šarić 2002). It seems that in cases of nouns that do not have a trace of “transfer” or “inalienability” which are low on the animacy scale (e.g. abstract nouns), the dative of possession meaning is more likely with clitic pronouns (mržnja mu ‘his hate’). The ethical dative (Peti Stantić 2000) is a “true” free dative, which gets realized with clitic forms of the first person singular and plural in sentences lacking verbs that take dative arguments (Nešto si mi neraspoložen, Jesi li mi se umorila?, Eto ti ga na vrata etc.), and in sentences with predicative verbs that do not take dative arguments (putovati ‘to travel’ Jesi li mi dobro putovala? or ušutjeti ‘stop speaking’ Nešto ste nam se ušutjeli.). The second person clitic pronoun, and non-clitic first and second person pronouns will be interpreted as ethical dative only under certain, strictly defined conditions (e.g. when an explicit reference to the subject is made Jesi li se ti meni umorila). Thus, there is a gradient of realizations of clitic and non-clitic pronouns that depends on an interplay of semantic and syntactic factors, with (1) the ethical dative which works on the information structure of the entire sentence and is linked by default to clitic pronouns, (2) the dative of possession which is semantically governed by a noun, and (3) patterns centered around the transfer prototype governed by verbs, nouns or adjectives and linked by default to non-clitic pronouns. Such an account of the Croatian dative is in line with accounts made for Czech by Fried (1999) and cross-linguistically by Shibatani (1994). References Dąbrowska, Ewa. 1997. Cognitive Semantics and the Polish Dative. Berlin, New York: Mouton de Gruyter. Fried, Mirjam. 1999. “From Interest to Ownership. A Constructional View of External Possession.” In External Possession, edited by Doris L. Payne and Immanuel Barshi, 473–504. Typological Studies in Language. Amsterdam, Philadelphia: John Benjamins. Jackendoff, Ray. 1990. Semantic structures. MIT Press. Jackendoff, Ray. 2002. Foundations of Meaning: Brain, Meaning, Grammar, Evolution. Oxford University Press. Janda, Laura A. 1993. A Geography of Case Semantics: The Czech Dative and the Russian Instrumental. Berlin ; New York: Mouton de Gruyter. Mikaelian I., and Roudet R. 1999. “Russkij dativ: ot adresata k sub’ektu” (“The Russian Dative Case: From the Recipient to the Subject”). Russian Linguistics, 23 (1999): 11-40. Shibatani, Masayoshi. 1994. “An Integrational Approach to Possessor Raising, Ethical Datives, and Adversative Passives.” Proceedings of the Annual Meeting of the Berkeley Linguistics Society: General Session Dedicated to the Contributions of Charles J. Fillmore 20 (1): 461–486. Peti-Stantić, Anita. 2000. “Etički dativ kao izraz gramatičke ekspresivnosti u jeziku.” In Riječki filološki dani: Zbornik radova s Međunarodnoga znanstvenog skupa Riječki filološki dani edited by Diana Stolac, 287-296. Rijeka: Filozofski fakultet. Stanojević, Mateusz-Milan, and Renata Geld. 2008. „The dative in Croatian as a dominion phenomenon“. Études cognitives 8: 95–108. Stanojević, Mateusz-Milan, and Nina Tuđman Vuković. 2012. „Dominion, subjectification, and the Croatian dative“. In Cognitive Linguistics between universality and variation, edited by Mario Brdar, Milena Žic Fuchs, and Ida Raffaelli, 93–116. Newcastle upon Tyne: Cambridge Scholars Publishing. Šarić, Ljiljana. 2002. “On the Semantics of the ‘Dative of Possession’ in the Slavic Languages: An Analysis on the Basis of Russian, Polish, Croatian/Serbian and Slovenian Examples.” Glossos 3. http://seelrc.org/glossos/.